HUBUNGAN ASUPAN KARBOHIDRAT SEDERHANA DAN LEMAK JENUH DENGAN KADAR TRIGLISERIDA PADA TENAGA KERJA PRIA DI CV LAKSANA KAROSERI - Pangesti, Nurma Bela; Mulyasari, Indri; Anugrah , Riva Mustika (JURNAL GIZI DAN KESEHATAN, 2019)
Background: Hypertriglyceridemia can be caused by excessive intake of simple carbohydrates and saturated fats. Hypertriglyceridemia must be considered as a serious health problem that affects employess productivity and company development. Objective: To analyze the relation between simple carbohydrates and saturated fats intake with triglyceride levels in male workers of CV. Laksana Karoseri Method :This research was cross sectional. Approach subject were 96 male workers aged 25-56 years with triglyceride levels ≥150 mg / dl that were taken using capillary blood collection method Random Sampling. Simple carbohydrate intake and saturated fat were calculated using the Recall method 3x24 hours. The normality test used Spearman Rho. (α=0,05). Results :The mean of subjects triglyceride levels was180 mg / dl ± 81.4 mg / dl, the mean of simple carbohydratesintake was27.18 gr ± 9.9, the mean saturated fat intake was38 gr ± 18.2. There wasa relation between simple carbohydrate intake and triglyceride levels (p = 0.040). There wasa relation of saturated fat with triglyceride levels (p = 0.014). Conclusion: There is a relation of simple carbohydrates with triglyceridelevels.There is a relation of saturated fat with triglyceride levels. Abstrak : Latar Belakang : Salah satu penyebab meningkatnya kadar trigliserida adalah asupan tinggi karbohidrat sederhana dan lemak jenuh. Hipertrigliseridemia pada pekerja merupakan masalah kesehatan yang harus diperhatikan dan berdampak pada produktivitas karyawan dan perkembangan perusahaan. Tujuan: Mengetahui hubungan asupan karbohidrat sederhana dan lemak jenuh dengan kadar trigliserida di CV. Laksana Karoseri. Metode: Jenis penelitian ini adalah cross sectional. Subjek 96 orang laki-laki berusia 25-56 tahun. Diambil menggunakan Random Sampling. Asupan karbohidrat sederhana dan lemak jenuh di ukur dengan menggunakan metode Recall 3x24 jam. Uji normalitas menggunakan Spearman Rho. (α = 0,05) Hasil: Rerata kadar trigliserida subjek yaitu 180 mg/dl± 81.4 mg/dl, rerata asupan karbohidrat sederhana yaitu 27.18gr ± 9.9, rerata asupan lemak jenuh 38 gr± 18.2. ada hubungan antara asupan karbohidrat sederhana dengan kadar trigliserida (p= 0.040). Ada hubungan lemak jenuh dengan kadar trigliserida (p=0,014). Kesimpulan: Ada hubungan karbohidrat sederhana dengan kadar trigliserida. Ada hubungan lemak jenuh dengan kadar trigliserida